Business Information Systems 14th International Conference, BIS 2011, Poznan, Poland, June 15-17, 2011. Proceedings - Abramowicz, Witold (Springer Berlin Heidelberg, 2011)
This book contains the refereed proceedings of the 14th International Conference on Business Information Systems, BIS 2011, held in Poznan, Poland, in June 2011. The 25 revised full papers were carefully reviewed and selected from 57 submissions. Following this year's conference theme of "Towards Flexible, Personalized and Adaptive Business Applications," the contributions were grouped into eight sections on business rules, business process verification, business process variants and composition, business process improvement, data modeling and integration, Internet science, modern enterprises, and specific business information systems issues.